DEVELOPMENT OF BIOLOGY INSTRUCTIONAL DESIGN USING PROBLEM BASED LEARNING (PBL) ASSISTED BY PODCAST AND GOOGLE CLASSROOM TO IMPROVE CRITICAL THINKING AND PROBLEM SOLVING SKILL OF SENIOR HIGH SCHOOL STUDENTS - Ratna Putri Kusuma Wardhani; Ibrohim Ibrohim (Universitas Muhammadiyah Semarang, 2021)
Technology development allows every individuals to learn from various learning sources and media especially during the COVID-19 pandemic that makes students have to study online from home. However, the implementation of online learning considered less able to improve students‟ 21 century skills especially critical thinking and problem solving skill. One of the learning models that can develop students‟ 21st century skills is PBL. The objectives of this research and development are (1) to produce instructional design which are syllabus, lesson plan, student‟s worksheet, assessment sheets, and podcast using PBL model and (2) to improve students‟ critical thinking and problem solving skill through the implementation of instructional design that have been prepared. The method of this research is Research and Development (R&D) with ADDIE model. The subject are students of XI MIPA 1 SMAN 1 Turen, Malang, East Java. Validation test result from the validators stated that the product has average score of 95.6% with very valid category. Practicality test result based on learning syntax implementation and students‟ response questionnaire consecutively has average score of 93% and 82% with very practical category. Effectiveness test gained from pretest, posttest, and calculation of N-gain has score of 0,3 for problem solving skills and 0,4 for critical thinking skills with moderate category. It can be concluded that (1) the instructional design have very valid and practical category to be implemented on biology learning process, and (2) students‟ critical thinking and problem solving skill improved after the implementation of the instructional design.Keywords: critical thinking, PBL, podcast, problem solving